Philip IV of Spain and the Portuguese Inquisition (1621–1641) - Paiva, José Pedro (2017)
The historiography of the Iberian Inquisitions has focused on analyzing relations between the Holy Office and the secular authorities in the society in which it operated. The Inquisition was not an island, it influenced and was influenced by society. This line of inquiry will be reprised to study relations between the Crown and the Portuguese Inquisition in a complex and difficult period in the history of the Hispanic monarchy, namely the reign of Philip IV, during which the kingdom of Portugal regained full independence in 1640. It will offer a holistic view of the institution (not restricted to policies designed to repress heresy), and a detailed reconstruction of events in order to demonstrate the dynamic nature of these processes. The essential problem will be to determine the impact of the Crown’s offensive, launched in an attempt to dominate the Tribunal, and the strategies and results of the response of the Inquisition, commanded by its Grand Inquisitors and the General Council of the Holy Office.